Recycling or organic waste generated in gastronomic activity - Chalón, Myriam (2011)
The solid waste generated in gastronomic activity, in our country, represents, a health problem. The solution could begin with a differential collection of these wastes and their recycling for specific purposes. The aim of this study was to design a culture medium for bacteria and fungi, whose nutrients came from organic waste generated in restaurants. The average percentage composition was: Crude protein 0.77 ± 0.18, dry matter: 1.53 ± 0.05, carbohydrates: 1.00 ± 0.03 and ash: 0.95 ± 0.14. This medium was used for biomass (bacteria and yeasts) and no significant differences (p > 0.05) were found in relation to commercial culture media, when were found in relation to commercial culture media, when Lactobacillus plantarum ATCC7469, Lactobacillus rhamnosus O236, Lactobacillus sp L46, Enterococcus sp C999, Staphylococcus aureus E2, Shigella sonnei S3, Salmonella enteritidis S4, Saccharomyces cerevisiae L1 and Schizosaccharomyces sp L2 were cultivated. The only organism included in this study, unable to develop in the culture media designed was Streptococcus Pa E1. The Streptococcus genus requires, for an optimal performance, complex media enriched with blood. Since the purpose of our study was to consider a minimal medium, blood addition was not considered, even knowing the nutritional requirements of this genus of bacteria. Our results allowed infer the conversion of organic waste in an alternative culture medium with a good yield in biomass. In addition, this medium showed some characteristics as accessibility (in any region of the country can be elaborated), low cost because, for processing, wastes generated in quantities and often highly were required; versatility (allows the growth of Gram-negative and Gram positive bacteria and also yeast). The single cell proteins have an important nutritional value due to high content of vitamins and lipids. Moreover these proteins present, in general, a whole set of essential amino acids. For this reason, yeast cells are usually used in animal feeding. The studies about technological process for elaborating the designed medium are in progress.